1978
DOI: 10.5271/sjweh.2693
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to styrene in a polymerization plant. Uptake in the organism and concentration in subcutaneous adipose tissue.

Abstract: Exposure to styrene in a polymerization plant. Uptake in the organism and concentration in subcutaneous adipose tissue. by Engström J, Åstrand I, Wigaeus E 4 (1978) 324-329. Three male employees exposed to styrene in the processing of polyester tanks were studied during a work week. From Tuesday to Friday the concentration of styrene in ambient air was measured continuously in the breathing zone. The uptake in the organism was estimated as the product of the time-weighted average of the concentration in insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 4 publications
(6 reference statements)
1
7
0
Order By: Relevance
“…This phenom enon suggests the existence of a body burden of styrene on Thursday. Such an accumulation of styrene during the workweek was not unexpected accordin g to pharmacokinetic data (29,30) and has also been reported earlier (7,14,31). We also observed that the intercept of the regression line of the afternoon was nearly 40% higher than that of the morning regression line.…”
Section: Discussionsupporting
confidence: 56%
“…This phenom enon suggests the existence of a body burden of styrene on Thursday. Such an accumulation of styrene during the workweek was not unexpected accordin g to pharmacokinetic data (29,30) and has also been reported earlier (7,14,31). We also observed that the intercept of the regression line of the afternoon was nearly 40% higher than that of the morning regression line.…”
Section: Discussionsupporting
confidence: 56%
“…The elimination of these solvents from adipose tissue in man is relatively slow (1,8,9,10,11,12), a phenomenon indicating a potential risk of prolonged exposure to such lipophilic solvents. In the present study mice were exposed to acetone, as it is of interest to compare the distribution and elimination pattern of the highly water-soluble acetone (19) with those of the earlier studied lipophilic organic solvents.…”
Section: Reprint Requests To: Ms E Wigaeus Researchmentioning
confidence: 99%
“…In the work environment styrene is absorbed primarily through the lungs with a small part coming through the skin (2-3). This highly liposoluble solvent is readily distributed to the blood (4), fat tissues (4), and the membranes of every tissue and organ.…”
mentioning
confidence: 99%